PENGARUH WORK LIFE POLICIES, WORK LIFE CONFLICT, JOB STRESS, DAN LONELINESS TERHADAP TURNOVER INTENTIONS PADA SEBUAH UNIVERSITAS SWASTA DI KOTA BATAM - Hielvita Ludiya (Jurnal Manajemen dan Pemasaran Jasa, 2016)
Turnover intention has been an important issue in any organization; management has long recognized that low turnover intention of employees is helpful for consequently obtaining high organizational performance and avoiding the potential costs related to recruiting and training new employees. This study aims to examine the impact of work life policies, work life conflict, job stress dan loneliness on turnover intentions at a private university in Batam. A total of 101 completed responses were collected in the survey. The sampling method in this research is done with the approach of non-probability sampling with the convinience sampling. The data analysis technique used was the technique of multiple regression analyisis. The findings of this research showed that work life policies and job stress have negative and significant impact on turnover intentions. Work life conflict and loneliness have positive and significant impact on turnover intentions. The managerial implications of this research have several limitations such as taking only one university and some faculties of full time lecturer which become the object of research. Moreover, researcher was not able to spend a lot of time at the organisation for collecting the data from the respondents. This research suggest that further investigation needs to be expanded by taking some of the objects that are similar research at the education industry or other industries, and by increasing the sample size to improve the results of consistency.